2022
DOI: 10.1177/26334941221080727
|View full text |Cite
|
Sign up to set email alerts
|

Controlled amnioreduction for twin-to-twin transfusion syndrome

Abstract: Background: Twin-to-twin transfusion syndrome (TTTS) is a severe condition causing preterm delivery, fetal death, and neurodevelopmental disorders. This study presents a data-based controlled amnioreduction (AR) protocol composed of sequential amniodrainage in treatment of TTTS. Methods: A total of 18 procedures were performed in 11 TTTS pregnancies at 17 to 34 weeks of gestation. The amniotic pressure was measured along with sequential removal of the amniotic fluid, 500 mL each step. The umbilical artery syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
2
0
3
Order By: Relevance
“…Additionally, septostomy and Fetoscopic laser surgery had a similar survival rate (70%). Studies to manage TTTS pregnancies showed an overall survival rate of twins in the range of 86.4% after AR [ 15 ] and 70–88% after Fetoscopic surgery [ 7 ], and 77% with expectant managing patients [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, septostomy and Fetoscopic laser surgery had a similar survival rate (70%). Studies to manage TTTS pregnancies showed an overall survival rate of twins in the range of 86.4% after AR [ 15 ] and 70–88% after Fetoscopic surgery [ 7 ], and 77% with expectant managing patients [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, amnioreduction had a lower survival rate (59%) than others. However, Gordon (2022) [ 15 ] reported that the controlled AR procedure resulted in a relatively high rate of twin survival (86%) with favorable long-term neurodevelopment outcomes. Therefore, the authors convinced that controlled AR procedures can be advised for managing TTTS pregnancies up to the 32nd week of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Jest powikłaniem u bliźniąt jednokosmówkowych dwuowodniowych, u których krew jest przenoszona od dawcy do bliźniaka biorcy poprzez zespolenia we wspólnym łożysku. [8] Zespół przetoczenia krwi między płodami (TTTS) Zespół ten powstaje w wyniku niezrównoważonego przepływu krwi między płodami przez obecne we wspólnym łożysku ( ciąża jednokosmówkowa) funkcjonalne połączenia naczyniowe.…”
unclassified
“…Obrócenie kranika o 90 stopni w kierunku przeciwnym do ruchu wskazówek zegara umożliwia drenaż owodniowy do worka. [8] Kontrolowana procedura AR, która polega na stopniowym drenażu płynu owodniowego z równoczesnym pomiarem ciśnienia usuwanej objętości ciśnienia owodniowego. Jak wykazały badania procedura ta ma stosunkowo wysoki odsetek przeżycia bliźniąt z korzystnymi długoterminowymi wynikami neurorozwojowymi.…”
unclassified
See 1 more Smart Citation